The Influence of Differentiated Learning Strategies by Paying Attention to Different Learning Styles of Students to Improve Science Learning Outcomes - Nanik Maryanti; E. Kus Eddy Sartono (Jurnal Penelitian Pendidikan IPA, 2024)
The study aims to examine the Influence of Differentiated Learning Strategies by Paying Attention to Different Learning Styles of Students to Improve Science Learning Outcomes. The study was conducted at SDN 2 Sanggrahan in grade VI students. The sampling technique used the purposive sampling area method. The study used a quasi-experimental design with data collection techniques through post-tests in the form of multiple choice and descriptive questions, observation, documentation and interviews. The data obtained were analyzed using statistical tests including normality tests, Data Analysis using Paired Sample t-Test. Based on the Validity Test, the results showed r = 0.82 α> (0.05) so that all question items showed valid results. Reliability test if the value of α> 0.738 the value is reliable, namely 0.789 Then the results of the normality test of the learning outcome value of 0.389> α (0.05) exceed the significant value, then the variable value is normally distributed, continued using the Paired Sample t-Test, the results of the t-test learning outcomes at a sig value of 0.00 <α (0.05) then reject H0. So it can be concluded that there is an Influence of Differentiated Learning Strategies by Paying Attention to Different Learning Styles of Students to Improve Science Learning Outcomes.